Transformasi Jajanan Tradisional: Strategi Pengembangan Produk Ongol-Ongol Berbasis Konsumen di Industri X, Gianyar - Jannati, Fitri Nur; Gede Wahyu Wardana; Dewa Ayu Anom Yuarini; Cokorda Anom Bayu Sadyasmara (SPECTA Journal of Technology, 2025)
Bali is renowned not only for its natural attractions but also as a culinary tourism destination rich in traditional foods. Gianyar Regency, a pioneer in gastronomic tourism, features ongol-ongol as a signature local product. Culinary enterprise X has produced ongol-ongol using traditional methods and inherited recipes since 2019. However, increasing competition led to a 15% monthly decline in sales during 2022–2023. This study aims to analyze consumer satisfaction to support market-oriented product development using the Quality Function Deployment (QFD) method. Data were collected from 94 respondents through a questionnaire evaluating seven product attributes: color, aroma, taste, texture, shape, size, and portion. Findings show that taste, portion size, texture, and aroma are considered the most important by consumers. Comparative analysis with competitors reveals that only the portion size attribute meets the satisfaction level of competitor products. Improvement ratio analysis indicates that none of the attributes have reached the desired satisfaction targets. Based on consumer perspectives, the priority for attribute improvement is as follows: aroma, taste, texture, color, shape, size, and portion. Key technical aspects requiring improvement include raw material preparation, dough mixing, and steaming processes. Recommended strategies for Enterprise X include: (1) implementing a grading system for cassava based on size, color, and ripeness; (2) adopting labeling to ensure raw material quality; (3) developing Standard Operating Procedures (SOPs) for dough mixing with clear ratios and timing; and (4) standardizing steaming procedures with specific time and temperature controls. These strategies aim to enhance product quality consistency and align with consumer expectations.